CGIAR’s Agroecology Initiative: transforming food, land, and water systems across the global South - Narjes, Manuel Ernesto; Quintero, Marcela; McCartney, Matthew P.; Wiederkehr Guerra, Gabriela Patricia (CGIAR System Organization, 2022)
This Initiative, called “Transformational Agroecology across food, land, and water systems” or more simply the CGIAR Initiative on Agroecology kicked off in Montpellier, France in March 2022. During this event, the Initiative Leadership Team highlighted the necessity for scientific evidence to show how agroecological principles applied in different socio-ecological systems are better able to provide equity, productivity, economic and environmental benefits than alternatives, including the status quo.